Insect-borne diseases in the 21st century - Nicoletti, Marcello (London, United Kingdom ; San Diego, CA : Academic Press, 2020)
Insect-Borne Diseases in the 21st Century provides a comprehensive look at the most notorious diseases carried by insects. It offers an assessment of current and potential insect-vectored diseases as they relate to human health and agricultural and livestock production. Written by a leading expert in insect-borne diseases, it examines the history of insect-borne diseases, beginning with those that have been well-known to scientists for decades, also including recent outbreaks like Zika. The book takes into consideration environmental conditions and climate change and explores the bionetworks and system biology of potential new superorganisms, offering preventative and protective solutions. This is a must-have resource for entomology researchers and students who seek the most up-to-date information on disease-causing pathogens transmitted by insects. This book will also serve as a resource for ordinary people whose lives may be affected by such diseases. --
Past, present, and future of insect-borne diseases -- Insect-borne diseases in the 21st century -- Insect-borne diseases in the 21st century -- Insect-borne diseases in the 21st century -- Insect-borne diseases in the 21st century -- Insect-borne diseases in the 21st century -- Insect-borne diseases in the 21st century.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on August 27, 2020).
WorldCat record variable field(s) change: 650
Keywords: Insects as carriers of disease -- 21st century; Communicable diseases -- 21st century; Insects as carriers of disease; Insect Vectors; Communicable Diseases; Communicable diseases; Insects as carriers of disease